Characterizations of bacterial pathogens isolated from internal organ of infected farmed freshwater fish - Sia, Siew Chuang; Samuel, Lihan; Tan, Cheng Siang; Chung, Hung Hui (2022)
The purpose of this study was to determine the prevalence pathogenic bacteria from various species of farmed freshwater fish and their antibiotic resistance patterns. Identification of the bacterial isolates was performed by GTG-PCR pattern analysis followed by 16S rRNA PCR sequencing. The antibiotic susceptibility test was performed by using the Kirby Bauer Disk Diffusion Method. In this study, the bacteria was randomly isolated from internal organ (liver, heart, kidney, internal organ fluid, eyeball fluid, and bile salt) of red tilapia (Oreochromis spp.), lampam (Puntius gonionotus), sultan fish (Leptobarbus hoevenii), patin (Pangasius spp.), and empurau (Tor tambroides). The bacteria acquired from the fishes were Aeromonas spp., Pseudomonas, Enterobacter, Citrobacter, Klebsiella, Plesiomonas, Enterococcus, and others. A total of 21 types of antibiotic were used in the susceptibility test and almost all of the bacteria strains were found to be resistant to two or three types of the antibiotics tested. The highest resistance was observed against Meropenem, Ertapenem, Ticarcillin and Imipenem among the tested bacteria. This indirectly showed the emerging multidrug resistant bacteria present in aquaculture of Borneo. In the future percept, the rapid diagnostic and treatment are essential as the view of the presence of the emerging multiantibiotic resistance bacteria.